Personalized management of atrial fibrillation: Proceedings from the fourth Atrial Fibrillation competence NETwork/European Heart Rhythm Association consensus conference. - Kirchhof, P; Breithardt, G; Aliot, E; Al Khatib, S; Apostolakis, S; Auricchio, A; Bailleul, C; Bax, J; Benninger, G; Blomstrom-Lundqvist, C; Boersma, L; Boriani, G; et al. (2013)
The management of atrial fibrillation (AF) has seen marked changes in past years, with the introduction of new oral anticoagulants, new antiarrhythmic drugs, and the emergence of catheter ablation as a common intervention for rhythm control. Furthermore, new technologies enhance our ability to detect AF. Most clinical management decisions in AF patients can be based on validated parameters that encompass type of presentation, clinical factors, electrocardiogram analysis, and cardiac imaging. Despite these advances, patients with AF are still at increased risk for death, stroke, heart failure, and hospitalizations. During the fourth Atrial Fibrillation competence NETwork/European Heart Rhythm Association (AFNET/EHRA) consensus conference, we identified the following opportunities to personalize management of AF in a better manner with a view to improve outcomes by integrating atrial morphology and damage, brain imaging, information on genetic predisposition, systemic or local inflammation, and markers for cardiac strain. Each of these promising avenues requires validation in the context of existing risk factors in patients. More importantly, a new taxonomy of AF may be needed based on the pathophysiological type of AF to allow personalized management of AF to come to full fruition. Continued translational research efforts are needed to personalize management of this prevalent disease in a better manner. All the efforts are expected to improve the management of patients with AF based on personalized therapy.